Investments in universal early childhood education - Sarah Sander (University of Copenhagen, Department of Economics, 2018)
This dissertation consists of three self-contained chapters on universal early childhood education. They complement each other by investigating three different perspectives of a large-scale investment in the rollout of universal daycare in Denmark during the late 1960s and 70s. Prior to 1964, subsidized childcare was targeted at single parents and parents, where they both had to work to make ends meet. This was changed in 1965, as the childcare regulations were changed to include subsidies to all families. Thus, by 1965, the Danish childcare system was changed from a targeted to a universal daycare system.
Keywords: 330